Effects of Energy Consumption, Economic Growth and Urbanization on Indonesian Environmental Quality - Purnama, Husna; Gunarto, Toto; Budiarty, Ida (International Journal of Energy Economics and Policy, 2020)
This study attempts to investigate the impact of urbanization on environmental degradation in the presence of economic growth, trade, and use of energy for Indonesia. For this purpose, this study uses CO2 emission as endogenous indicators and GDP per capita, the use of energy, urbanization, and trade liberalization as exogenous indicators. Annual time series data are taken from World Development Indicators (WDI) for the period of 1970 to 2018. First of all, in order to check the characteristics of the indicator ADF and PP unit root tests are applied. Results indicate that Trade and Urbanization are stationary at a level while rests of all are at first difference. Further, the study uses the ARDL-bound test to check the co-integration in the model and verifies the existence of co-integration. The long run results are estimated by ARDL methodology. Results confirmed that there does not exit the EKC hypothesis in Indonesia because economic growth boosts the carbon production level in Indonesia. Energy consumption also creates environmental degradation while trade decreases the carbon emission level. Urbanization has not significantly influenced the level of the environment. It is just because of the country's high urban development, energy use is still less due to the less income of the majority of population, and this may be one of the explanations why urbanization is not affecting the country's carbon dioxide pollution. Keywords: Emission of CO2, Urbanization, Use of Energy, ARDL, Development of Economy, Indonesia JEL Classifications: Q56, N7 DOI: https://doi.org/10.32479/ijeep.10586